Teaching Grammar: Degrees of Adjective Comparisons in Secondary School of Indonesian Context - Muflihun Muflihun (Institut Agama Islam Negeri Palopo, 2019)
This article explores the teaching grammar in secondary school in Indonesian context, the writer noticed that most of the students were struggling to clearly understand and unable to use comparison of adjective. Therefore, the writer would clearly explain those problems supported by research findings from previous studies. There are several activities to be used in teaching grammar, which surely could also be adapted to teaching adjective comparisons. However, in this essay, the writer would only address two common activities; namely grammar games and discovering grammar. It can be concluded that teaching grammar to some extent would not be complicated if it is delivered though appropriate teaching methods and deeply understand students’ problems. Numerous engaging activities to teach grammar is available and this would shift our common paradigm of seeing learning and teaching grammar as a passive and ‘old’ fashioned thing to more communicative grammar teaching and learning.